Right atrial epithelioid angiosarcoma with multiple pulmonary metastasis confirmed by multimodality imaging-guided pulmonary biopsy: A case report and literature review. Issue 30 (July 2018) - Liu, Cuiwei; Zhao, Yanxia; Yin, Zhongyuan; Hu, Ting; Ren, Jinghua; Wei, Jielin; Xie, Linka; Xiong, Jie; Wu, Hongge; Dai, Xiaofang; Fei, Shihong
Abstract: Rationale: Primary cardiac tumors are very rare, and angiosarcoma accounts for about 33% of all primary malignant cardiac tumors. Primary cardiac epithelioid angiosarcoma is a highly aggressive and difficult to diagnose tumor, with early systemic metastasis and poor prognosis. Patient concerns: A 35-year-old Han male experienced sudden severe palpitation and moderate dyspnea. The patient received a whole body F-18 fluoro-deoxyglucose positron emission tomography (18F-FDG PET)/computed tomography (CT) scan, the scan showed a large mass in the right atrium (RA) and numerous pulmonary nodules in both lungs. Diagnoses: The patient was diagnosed as right atrial epithelioid angiosarcoma with multiple pulmonary metastasis by pulmonary biopsy through CT-guided percutaneous transthoracic fine needle aspiration. Interventions: The patient received a cycle of chemotherapy with docetaxel and gemcitabine, followed by another cycle with epirubicin and ifosfamide. Outcomes: The chemotherapy was ineffective. After the two cycles, the bilateral pleural effusion steadily increased, the patient had severe dyspnea and palpitation, and died three weeks later, with an overall survival of 2.5 months. Lessons: Primary angiosarcoma of heart is a very rare and aggressive disease, and its diagnosis and treatment are difficult. Most patients may have systemic metastasis at diagnosis, and have a very short survival without surgical resection. Hence, early diagnosis and surgical resection is extremely important to treat this disease.